Introduction to sociological theory theorists, concepts, and their applicability to the twenty-first century - Dillon, Michele,1960 (Chichester, West Sussex, United Kingdom Wiley Blackwell, 2014)
The extensively revised and updated second edition combines carefully chosen primary quotes with wide-ranging discussion and everyday illustrative examples to provide an in-depth introduction to classical and contemporary sociological theory.Combines classical and contemporary theory in a single, integrated text. Short biographies and historical timelines of significant events provide context to theorists' ideas. Innovatively builds on excerpts from original theoretical writings with detailed discussion of the concepts and ideas under review.
Karl Marx -- Emile Durkheim -- Max Weber -- Talcott Parson and Robert Merton : functionalism and modernization -- Critical theory : technology, culture, and politics -- Conflict, power, and dependency in macro-societal processes -- Exchange, exchange network, and rational choice theories -- Symbolic interactionism -- Phenomenology and ethnomethodology -- Feminist theories -- Michel Foucault : theorizing sexuality, the body, and power -- Race, racism, and the construction of racial otherness -- The social reproduction of inequality : Pierre Bourdieu's theory of class and culture -- Economic globalization -- Modernities cosmopolitanism, and global consumer culture.
Includes bibliographical references and index.
Keywords: Sociology; Sociology -- History